Diversity and Development Futures in the Education of Adults. Proceedings of the Annual Conference (26th, Leeds, England, July 2-4, 1996) - Standing Conference on Univ. Teaching and Research in the Education of Adults; Zukas, Miriam; Standing Conference on Univ. Teaching and Research in the Education of Adults ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
Fifty-three papers are included in this proceedings. They include: "Power, Peers and Professional Development" (Armstrong, Zukas); "Invent Your Future, Reinvent Your Past" (Armstrong); "Managing Learning Organisations" (Barron); "Adult Learning, Cultural Diversity and Ethnoknowledge" (Benn); "Culture of Computer Technology in Education and Research" (Blanchette); "Use of Problem-Based Learning in the Education of Adults in Part-Time Higher Education" (Bowden, Newton); "Open and Flexible Provision" (Calder, McCollum); "Open Learning Workshops" (Cashin); "Knowledge in an Age of Uncertainty" (Chappell); "Combining Arts and Adults" (Chapple); "Stories We Tell Them?" (Chase); "Email Conferencing" (Davis); "Performance, Quality and Community in Adult Community Education" (Emsley);"Changes in British University Adult Education" (Fang); "Historical Perspective on Future Developments and Diversity in British Adult Education" (Fieldhouse); "Diversity and the Quality Debate" (Gardiner); "From Backwater to Mainstream" (Hampton); "Function , Fascination and Facilitation of Reflective Practice in Continuing Professional Education" (Hunt); "Community Educators" (Jarvis, Notley); "European Involvement in the Future of Education of Adults in England and Wales" (Jarvis, Dubelaar); "Different Context: Same Praxis?" (Jones); "Case Study in Postmodern Pedagogy for Graduate Education" (Kasl, Elias); "Working Class Women in Further Education" (Kilminster); "Adults@Learning.net" (McConnell); "Networked Learning" (McConnell); "Recognising Diversity" (Macdonald); "Futures in the Education of Educators" (Malcolm); "Future for Professional Learning" (Millar, Smith); "Transformation, Multiculturalism, and Community" (Multicultural Inquiry Exchange [MIX]); "Getting to Grips with Barriers to Reflection" (Newton); "Is There a Future for Community in Continuing Education?" (O'Rourke); "Assessing Values" (Patel); "Guidance" (Payne); "Positions of Race and Gender in Adult Continuing Education" (Preece); "Searching for the 'Pluriverse'" (Rose); "Learning the Business of Business" (Schwenke, Schwenke); "Fitness for Purpose in Continuing Professional Education" (Smith); "Local Government Reorganisation" (Spackman, Paul); "Future of University Continuing Education" (Taylor); "Experience Never Ends" (Thomson); "Women in Further Education" (Wallis); "Professional Development and Mentoring for Under-Represented Minority Faculty" (Williams, Crandall); "Can Post-Modern Adults Be Educated? (Wiltsher); and "Should Higher Education for Adults Carry a Health Warning for Their Relationships?" (Wray). (MN)
Availability: S.C.U.T.R.E.A., Division of Adult Continuing Education, University of Sheffield, 196-198 West Street, Sheffield S1 4ET, England, United Kingdom (15 British pounds).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Adult Educators; Adult Learning; Case Studies; Community Education; Computer Uses in Education; Continuing Education; Cultural Differences; Education Work Relationship; Educational Administration; Educational Change; Educational Needs; Educational Objectives; Educational Practices; Educational Research; Educational Trends; Electronic Mail; Foreign Countries; Futures (of Society); Higher Education; Humanities; Instruction; International Educational Exchange; Multicultural Education; Open Universities; Part Time Students; Peer Relationship; Problem Solving; Professional Continuing Education; Teacher Education; Workshops; Great Britain; Canada -- Europe; Collected Works, Proceedings; Reports, Research